A Triple-Band Slotted Patch Antenna With Metasurface Loading for UHF-RFID, Satellite Communication, and 5G Applications - Sayan Sarkar; Bhaskar Gupta (IEEE Access)
A triple-band, coaxial-fed, slotted microstrip patch antenna with metasurface loading is presented in this article. The first frequency band covers the 865-868MHz European UHF-RFID band, the second frequency band partially covers the 3300-4200MHz n77 and 3300-3800MHz n78 5G communication bands. Finally, the third frequency band partially covers the 3.7-4.2GHz satellite communication band. The S $_{11} \le -10$ dB regions of the antenna-metasurface system lie between 833-885MHz, 3400-3550MHz and 4059-4164MHz. The system exhibits right circular polarization within the first and third frequency bands with a 3dB axial ratio bandwidth of 41MHz (5%) within the first band and 111MHz (2.7%) within the third band. The 3dB axial ratio beamwidth is $± 60^{0}$ within the RFID band and $± 30^{0}$ within the satellite communication band. Moreover, the system also exhibits a dual-linear polarization within the second band. The radiation efficiency remains within the 75-85% region for all the three bands. The dimensions of the system are $0.28λ _{0}$ x $0.28λ _{0}$ x $0.023λ _{0}$ at 865MHz. The proposed antenna-metasurface system is therefore very versatile, finding use as an UHF-RFID reader as well as for 5G and satellite communication.